Hearts for horses: a fun rehabilitation for dyslexia - Kunasegran, Kavenia; Subramaniam, Vijayaletchumy (Human Resource Management Academic Research Society, 2020)
The purpose of this study was to investigate parents’ perceptions and experiences of equine therapy for their dyslexic children. Twenty-four children were recruited from Malaysia Dyslexia Association in administering equine therapy. The research participants were parents of children with dyslexia. A sample size of twelve parents were therefore selected for the study. To complete this study, three modes of data collection was carried out, namely through observations, surveys and interviews. In this study, the researcher applied triangulation data by collecting three forms of data sources, namely questionnaires, audio and video recording and research field notes to increase validity and reliability of the research. Parents of the children in the treatment group gave feedback on their experience of equine therapy. Results from the parents demonstrated that their child has shown significant improvement in the following aspects, 1) physical & motor skills, (2) psychological, (3) social, and (4) cognitive. The findings showed that this unique intervention has improved them directly in a fun and new rehabilitation. The majority of the parents felt that the equine therapy was effective in treatment of learning difficulties.